Putative role of corazonin in the ovarian development of the swimming crab Portunus trituberculatus - Tu, Shisheng; Ge, Fuqiang; Han, Yaoyao; Wang, Mengen; Xie, Xi; Zhu, Dongfa (Frontiers in Marine Science, 2022)
Corazonin (Crz) is a neuropeptide that widely distributed in insects and crustaceans. The Crz is proposed to have pleiotropic functions in insects, but its physiological roles in crustaceans are poorly understood. In the present study, Crz and its putative receptor (CrzR) were identified from the swimming crab, Portunus trituberculatus, and their interaction was validated using the Dual-Luciferase reporter assay system. Tissue distribution analysis showed the PtCrz was mainly derived from center nerve system, while its receptor was highly expressed in Y-organ, the main site for ecdysteroids synthesis. Exposure of YO to synthetic Crz and CrzR dsRNA respectively led to the transcriptional changes of two ecdysteroidogenesis genes, further indicating a putative role of Crz signaling on ecdysteroids synthesis. During the ovarian development, the mRNA levels of PtCrz and PtCrzR increased significantly in vitellogenic stages, suggesting a potential role of Crz signaling in vitellogenesis. The hypothesis was further strengthened by in vitro experiments that the expression of vitellogenin (Vg), Vg receptor (VgR), cyclinB, and Cdc2 in ovary explants could be induced by synthetic Crz, whereas reduced by CrzR dsRNA. In addition, since 20-hydroxyecdysone also showed a stimulating effect on Vg expression, an indirect regulation of Crz signaling on ovarian development via ecdysteroids might also exist.